Religion, identity and politics in Northern Ireland: boundaries of belonging and belief - Mitchell, Claire (Ashgate, 2006)
Introduction: The nature of the conflict -- The 'sectarian headcount' -- The churches and politics -- Religion as a boundary marker -- Religious practice and community construction -- Religious ideology and politics -- Theology and politics -- Conclusions.